Examining the Implementation of the Independent Learning Curriculum in English Language Material at Vocational High Schools - Purwo Haryono (AL-ISHLAH: Jurnal Pendidikan, 2024)
The teacher's task in the Merdeka Belajar curriculum is to prepare learning plans, materials, and methods, and assess them. However, out of 50 students, there were 32 people whose mean score was below the standard of 75, namely 28.30. Another point, 40% cannot complete the English material test. It is urgent to research because there are gaps in theory, expectations, and reality in the field to find out the results of the analysis of obstacles and difficulties in implementing the independent learning curriculum on English language material. Mixed methods research method. The subjects were 120 vocational high school students. Data collection techniques use surveys and interviews. Instruments are arranged based on indicators. Instruments are shared via a Google Form link. Interviews were conducted to strengthen the survey results. The analysis technique uses SPSS version 26.0. Interview data was analyzed by collecting data, reducing, and drawing conclusions. The results showed that 39.17% of teachers had prepared learning plans, only 31.68% were able to deliver the material, only 44.12% were able to assess, only 39.17% of students experienced changes in behavior and 49.18% evaluated the English curriculum material. Freedom to learn. Consistent with the interview data, the survey confirms that instructors are still struggling to put the curriculum into practice. Many of those who took the survey are looking forward to receiving instruction on how to use the Merdeka curriculum to teach English, as well as how to evaluate and assess previously taught courses.